Decolonizing Constitutional Democracy: Reconfiguring Indonesia's Presidential Election System from the Perspective of Siyasah Syar'iyyah - Any Ihsany Nasution; Mustafa Lutfi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This study aims to reassess the Indonesian presidential electoral system within the context of postcolonial liberal democracy and to propose an alternative democratic framework rooted in the values of siyasah syar'iyyah (Islamic political governance) as part of the decolonization of Islamic politics. The main issues addressed include presidential conflicts of interest during election campaigns, weak electoral oversight institutions, and regulatory ambiguities that allow ethical distortions in democratic practices. The research adopts a normative-juridical approach combined with a conceptual analysis of siyasah shar'iyyah. Data were collected through the examination of electoral laws, academic literature, and classical Islamic political thought such as Al-Ahkam al-Sultaniyyah, Siyasah Syar'iyyah, and Al-Muwafaqat. A qualitative juridical analysis was employed to evaluate the alignment between positive legal norms and the principles of Islamic governance. The findings reveal a fundamental misalignment between Indonesia's electoral practices and the core Islamic political values of justice ('adl), integrity (amanah), and public welfare (maslahah). The phenomenon of presidential intervention in campaigns (cawe-cawe) signifies an ethical leadership crisis, legitimized by vague regulations and weak institutional checks. The study recommends the reconfiguration of Articles 281, 282, and 299 of Law No. 7/2017 as a normative measure to enforce political neutrality and prevent abuse of power. Theoretically, this research contributes to the discourse on decolonization in Islamic political studies and constitutional law. The siyasah syar'iyyah framework provides a more substantive and contextually grounded ethical paradigm than liberal democratic proceduralism and offers a pathway for integrating Islamic values into modern Indonesian political systems.